2021
DOI: 10.1101/2021.01.08.425965
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular Dynamics Analysis of a Flexible Loop at the Binding Interface of the SARS-CoV-2 Spike Protein Receptor-Binding Domain

Abstract: Since the identification of the SARS-CoV-2 virus as the causative agent of the current COVID-19 pandemic, considerable effort has been spent characterizing the interaction between the Spike protein receptor-binding domain (RBD) and the human angiotensin converting enzyme 2 (ACE2) receptor. This has provided a detailed picture of the end point structure of the RBD-ACE2 binding event, but what remains to be elucidated is the conformation and dynamics of the RBD prior to its interaction with ACE2. In this work we… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…[ 24 , 26 ]. Several structural and dynamic studies at the molecular level show that SARS-CoV-2 RBDs have to adapt open conformation (also known as “up” or “standing”) to effectively bind to ACE2 receptors [ 8 , 16 , 61 , 62 ]. So far, mutations in non-RBD residues, such as the D614G variant, can populate RBD open conformation rather than closed conformations [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 24 , 26 ]. Several structural and dynamic studies at the molecular level show that SARS-CoV-2 RBDs have to adapt open conformation (also known as “up” or “standing”) to effectively bind to ACE2 receptors [ 8 , 16 , 61 , 62 ]. So far, mutations in non-RBD residues, such as the D614G variant, can populate RBD open conformation rather than closed conformations [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mutation of alanine instead of tyrosine at 501 (i.e., N501A) shows an increase in loop Y473–C489 flexibility and conformational compactness according to a related study [ 61 ]. Moreover, the same loop Y473–C489 in SARS-CoV RBD showed a higher flexibility in comparison to SARS-CoV-2 RBD [ 61 , 62 ]. This suggests that the higher infectivity of the N501Y variant might be attributed to an improvement in the N501Y RBD conformation and therefore a higher affinity to ACE2 receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, study revealed that the loop 3 and 4 regions are more flexible domains at the RBD (Williams et al, 2021). Upon the closer observation, the residue flexibility trajectories also reflected to have higher flexibility at the region of 470 -490.…”
Section: Resultsmentioning
confidence: 82%
“…This large shift was enhanced by five glycan residues bound to Asn53, Asn90, Asn103, Asn322, and Asn546 of ACE2, with Asn53 involved in both intramolecular homodimer and heterodimer contacts. [27,28] Williams and coworkers [29] suggested that in the RBD:ACE2 interaction pattern, residues Phe486, Asn487, and Tyr489 are responsible for the adaptive flexibility of RBD in establishing strong interactions with ACE2. At the same time, this study demonstrated how mutations in that RBD sub-region are crucial in the selective pressure of the virus, altering the flexibility of RBD and interfering in intra-monomer interactions within the RBD.…”
Section: Molecular Dynamics Simulations Uncover the S Protein Flexibi...mentioning
confidence: 99%
“…At the same time, this study demonstrated how mutations in that RBD sub-region are crucial in the selective pressure of the virus, altering the flexibility of RBD and interfering in intra-monomer interactions within the RBD. [29]!From a geometric perspective, effective interaction between SARS-CoV-2-spike and ACE2 would occur at an angle of inclination between the apical portion of RBD "up" and ACE2 of at least 52°. [30] Such MD results indicated that RBD "up" conformations have a large degree of manoeuvre to achieve sufficient residue exposure for ACE2 binding.…”
Section: Molecular Dynamics Simulations Uncover the S Protein Flexibi...mentioning
confidence: 99%